PENGARUH TEKNIK PENYADAPAN TERHADAP PRODUKSI GETAH AGATHIS DI BALI - Ishak Sumantri Sumantri; Dulsalam Dulsalam; Machfudh Machfudh (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
There are many kinds of Agathis sp. having specific bark thickness in Indonesia. For example, at Buleleng Forest District Bali, where the investigation was carried out, there are two groups of Agathis sp. The first group is Agathis sp. known to have bark thickness greater than one cm, and the other group belongs to thin bark ( < 1cm). The bark thickness of Agathis sp. has a bearing on the resin yield. The resin itself is always coagulated quickly, there by requiring special treatment to produce optimal resin yield. This investigation is intended to select the Agathis sp. producing optimum resin yield and to increase the resin output by applying new tapping technique. This study reveals that:The resin yield of Agathis sp. in Bali was quite low. It ranges from 0.1 gram to 24.6 gram/tree/week with approximately 3.8 gram/tree/week average.Agathis sp. with thick bark give higher resin yield than those of thin bark. The average resin yield of thick bark Agathis sp, was 6.3 gram/tree/week, while it is only 1.3 gram/tree/week for thin bark.The V-shape tapping method give resin yield approximately 80% higher than the reverse V-shape.The application of H2SO4 10% as stimulant did not give significant effect on the resin production. Based on the average resin yield data, however, the resin yield was actually increased approximately 26% when the H2S04 were added compare to the control.